2010
DOI: 10.1002/chem.201000063
|View full text |Cite
|
Sign up to set email alerts
|

Quinaphos and Dihydro‐Quinaphos Phosphine–Phosphoramidite Ligands for Asymmetric Hydrogenation

Abstract: New derivatives of the Quinaphos ligands and the related Dihydro-Quinaphos ligands based on the more flexible 1,2,3,4-tetrahydroquinoline backbone have been prepared and fully characterised. A general and straightforward separation protocol was devised, which allowed for the gram-scale isolation of the R(a),S(c) and S(a),R(c) diastereomers. These new phosphine-phosphoramidite ligands have been applied in the Rh-catalysed asymmetric hydrogenation of functionalised olefins with the achievement of excellent enant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…The comparison of these findings with the calculated proton distances (Table 2) clearly indicates that the diastereomer formed has the absolute configuration ( S C2 , R a ). This assignment is in full agreement with the trend observed for the through‐space P,P′ coupling constants of L3 ( J =188.3 Hz) and L4 ( J =153.3 Hz), which fits perfectly with the values measured for the structurally related ( S C2 , R a )‐1‐naphquinaphos ( J =209.6 Hz) and ( R C2 , R a )‐1‐naphquinaphos ( J =151.5 Hz) 3d…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The comparison of these findings with the calculated proton distances (Table 2) clearly indicates that the diastereomer formed has the absolute configuration ( S C2 , R a ). This assignment is in full agreement with the trend observed for the through‐space P,P′ coupling constants of L3 ( J =188.3 Hz) and L4 ( J =153.3 Hz), which fits perfectly with the values measured for the structurally related ( S C2 , R a )‐1‐naphquinaphos ( J =209.6 Hz) and ( R C2 , R a )‐1‐naphquinaphos ( J =151.5 Hz) 3d…”
Section: Resultssupporting
confidence: 89%
“…Following an original protocol,5 quinaphos ligands are accessible as a diastereomeric mixture through a one‐pot synthesis that started from 8‐bisarylphosphinoquinoline. Recently, a general separation procedure was developed to enable the isolation of diastereomerically pure quinaphos on a gram scale 3d…”
Section: Introductionmentioning
confidence: 99%
“…Considering the structural similarity to enamides, which could be hydrogenated with high enantioselectivities with Rh/phosphine–phosphoramidites catalysts,21, 22b we decided to examine ( R a , S c )‐1‐Naph‐QuinaPhos L1 and ( S a , S c )‐MatPhos L2 in the Rh‐catalysed asymmetric hydrogenation of 1‐alkyl vinyl esters. The substrates were prepared either from the corresponding ketones by acid‐catalysed acylation with isopropenyl acetate9 or by the Ru‐mediated addition of carboxylic acids to alkynes developed by Gooßen and co‐workers.…”
Section: Methodsmentioning
confidence: 99%
“…20 The magnitude of phosphorus through-space coupling constants can have the range from 1 to 10 Hz in the case of bisphosphites, 21 74-76 Hz for tetraphosphine ferrocenyl derivatives 22 or even extremely high values of 131-209 Hz as observed in Quinaphos derivatives. 23 Szalontai et al demonstrated that flexible bisphosphites show a decreasing coupling with increasing temperature. 21 Our 31 P{ 1 H}-NMR measurements of 2 showed decreasing coupling constant with increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Anal. Calcd for C 23 (2S,4S)-Dimethyl-2-diphenylphosphino-4-anilinopentane 4d (0.97 g, 2.792 mmol) in 20 mL of abs. THF was added dropwise to the stirred solution of PCl 3 (365 lL, 4.188 mmol) and triethylamine (677 lL, 4.88 mmol) in 5 mL of THF over 20 min at À20°C.…”
Section: (2s4r)-2-(benzilamino)-4-sulfato-pentane 3cmentioning
confidence: 99%